Plant extracts as an alternative for antibiotics in Saanen goats’ semen extender - Shikh Maidin, Mashitah; Mohammed, Nur Hafizah; I., Siti Syamsiah; M., Noor Izza; M. I., Norzuraiti (Malaysian Agricultural Research and Development Institute (MARDI), 2024)
The widespread use of antibiotics contributes to the development of antibiotic resistance. Therefore, exploring suitable alternatives to antibiotics is crucial. This study aimed to determine the antibacterial effect of mulberry, roselle and aloe vera extracts on bacteria isolated from buck semen and their effectiveness as an alternative to antibiotics for semen extender. The antibacterial activity of plant extract against identified bacteria was determined by using disc diffusion method. Semen was added to the extender with mulberry, roselle or aloe vera extract and incubated at 37 °C for 3 h and cryopreserved for 24 h before the assessment of bacterial load and semen quality were investigated. Results shows that mulberry extract was the only plant extract that significantly inhibited both gram-negative and gram-positive bacteria, with greater inhibitory zone on gram positive bacteria (22.33 ± 1.12 mm) compare to Roselle (8.1 ± 1.08 mm) and Aloe vera (9.6 ± 1.05 mm) resulting in the lowest bacterial load (763 ± 4.57 CFU/ml) and improved sperm quality during the 3-hour incubation period. Whereas, aloe vera and roselle extracts were highly effective for decreasing bacterial contamination and protecting the sperm quality of post-thawed semen. The study concluded that, mulberry extract was a suitable alternative to commercial antibiotics for fresh semen extenders, while aloe vera and roselle were more recommended for cryopreservation purposes.